African policy of Delhi and Indian community in Africa: current status - Vyacheslav Alexandrovich Usov (Vestnik RUDN. International Relations, 2016)
The article is devoted to a changing nature of India-Africa relations and a role of Indian Diaspora in Africa. Indian Diaspora in African countries for many years was regarded by the Indian government more as a stumbling block for development India-Africa relations than as a source of opportunities. New policy to Diaspora was elaborated in the very beginning of 2000s but it was Narendra Modi, Indian prime-minister from 2014, who started promoting Diaspora as one of the priority in his international agenda. Indian government initiated in October 2015 third India-Africa Forum-Summit which happened to be much larger event than two previous forum summits in 2008 and 2011. However energetic policy of N. Modi has not brought India-Africa relations to a new level yet. While planned visit of N. Modi to a number of African countries in July 2016 is seen as a step to achieve this goal, his meetings with representatives of Indian communities in these African countries could be regarded as a sign of a new approach to the Indian Diaspora as “Ambassadors of India”. That could bring some controversy as many South African Indians consider themselves only citizens of their country and no more. Besides, the Indian government should take all necessary measures to prevent racist attacks against Africans in India which greatly tarnish the Indian image in the eyes of Africans.